EKSPLORASI SIFAT FISIKOKIMIA 2-BENZILIDEN-SIKLOHEKSANA-1,3- DION BERDASAR PERHITUNGAN KIMIA KUANTUM SEMIEMPIRIK - Enade Perdana Istyastono (Universitas Islam Indonesia, 2006)
ABSTRACTAromatic cyclic endione has been predicted qualitatively as anticancer agent. 2-Benzylidenecylclohexane-1,3-dione is the simplest aromatic cyclic endione compound. Physicochemistryproperties of 2-benzylidene-cylclohexane-1,3-dione have been explored. The properties wereexplored by semiempirical quantum-chemical calculations using the computational chemistryapproach. Vibrations spectrum of 2-benzylidene-cylclohexane-1,3-dione has been used todetermine the best semiempirical method. The AM1 semiempirical method was found to be themost appropriate method to describe the structure of 2-benzylidene-cylclohexane-1,3-dione andexplore the physicochemistry properties.Keywords : anticancer, physicochemistry, semiempirical quantum-chemical calculation, 2-benzylidene-cylclohexane-1,3-dione.